Reflections on incorporating climate change considerations in environmental impact assessment - Gajardo Matthews, Paula (Revista de Derecho Ambiental, 2019)
The purpose of this paper is to analyze the manner in which climate change is considered, or should be considered, in the Chilean Environmental Impact Assessment System. Although there seems to be some consensus regarding the fact that the regulatory framework associated with the Environmental Impact Assessment System does not currently contemplate the possibility of evaluating variables associated with climate change, it is possible to observe a series of international instruments that incorporate or recommend incorporating considerations related to this phenomenon in the environmental assessment process. Based on the foregoing, a set of comparative experiences, especially instruments developed by international organizations, were reviewed in order to identify the main issues that should be taken into consideration so as to integrate climate change into environmental impact assessment processes in Chile. It concludes that it is probable that this will imply introducing relevant modifications to the environmental assessment process as we know it, we consider this is fully justified, given the urgency and magnitude of the challenge that climate change represents.